THE COLLABORATIVE POLES NETWORK AND THE DEVELOPMENT OF AN EFFICIENT ENTREPRENEURIAL ECOSYSTEM - Roxana VOICU-DOROBANŢU; Aron JINARU; Alexandru CARAGEA (SEA: Practical Application of Science, 2014)

(untitled)
The experience of the past decades has shown that the key features that foster innovation and entrepreneurship are: a dense concentration of human talent, a competitive spirit, easy access to capital, and a supportive environment. It also notes that, to some extent, these can be replicated in and adapted to a wide variety of contexts, even in countries and regions with economies, politics and cultures sharply divergent from the Silicon Valley California generic model. In all these cases, innovative business accelerators are functional and located in areas with critical masses of talent and competitive spirit. In this theoretical paper we show that a network accelerator could be a solution for fostering innovation and entrepreneurship in less developed regions and for attracting further venture-capital investors. This work has been supported by SNF and UEFISCDI within the Romanian-Swiss Joint Research Project IZERZ0 142306 / 1.